2023
DOI: 10.3390/f14061252
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Estimation of Chinese Fir Stand Volume Based on UAV-LiDAR Technology

Abstract: Chinese fir (Cunninghamia lanceolata) is the main fast-growing timber species in China, and studies of its stand volume are important for evaluating the effectiveness of forest management. However, it is difficult to accurately estimate stand volume from the perspective of a single tree due to the mutual concealment among Chinese fir trees. Therefore, in this study, we propose a method for identifying different forms of Chinese fir. The specific idea is to realize the accurate identification of a single Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this study, we also found that the insensitivity of the traditional K-means method to point cloud height made it difficult for the algorithm to identify suitable clustering positions, ultimately leading to frequent over-segmentation (Figure 8) [25]. As shown in the figure, the single-tree segmentation result (circled in white) includes part of the crowns of the other trees.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we also found that the insensitivity of the traditional K-means method to point cloud height made it difficult for the algorithm to identify suitable clustering positions, ultimately leading to frequent over-segmentation (Figure 8) [25]. As shown in the figure, the single-tree segmentation result (circled in white) includes part of the crowns of the other trees.…”
Section: Discussionmentioning
confidence: 84%